1986
DOI: 10.3102/00028312023002263
|View full text |Cite
|
Sign up to set email alerts
|

Maps, Mode of Text Presentation, and Children’s Prose Learning

Abstract: This study examined the effects of reference maps on what children remember from written and aurally presented discourse. Subjects were presented one of three maps that varied in feature configuration and spatial distribution, and were asked to study these maps before reading or listening to a related story. Results of tests across both prose and maps conflicted with previous research in which learners appeared unable to maintain visual images while reading. We found essentially no differences in recall due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…Of further surprise was the absence of notable differences in story recall between the Map and List conditions, particularly given the numerous studies that have reported greater prose learning when map features are spatially distributed versus merely listed (Abel & Kulhavy, 1986;Mastropieri & Peters, 1987;Schwartz & Kulhavy, 1981). A reasonable explanation for this finding is that criterion measures on the post-test were unrelated to the keywords that constituted the map features.…”
Section: Rated Usefulness Of Materials and Proceduresmentioning
confidence: 57%
See 3 more Smart Citations
“…Of further surprise was the absence of notable differences in story recall between the Map and List conditions, particularly given the numerous studies that have reported greater prose learning when map features are spatially distributed versus merely listed (Abel & Kulhavy, 1986;Mastropieri & Peters, 1987;Schwartz & Kulhavy, 1981). A reasonable explanation for this finding is that criterion measures on the post-test were unrelated to the keywords that constituted the map features.…”
Section: Rated Usefulness Of Materials and Proceduresmentioning
confidence: 57%
“…of display components (Kulhavy & Schwartz, 1980;Winn, 1988;Winn & Sutherland, 1989). A good example of research in this area can be seen in several map studies conducted by Kulhavy and his colleagues (Abel & Kulhavy, 1986;Kulhavy & Schwartz, 1980;Kulhavy, Schwartz, & Shaha, 1983;Schwartz & Kulhavy, 1981) that found subjects were signifIcantly better at recalling map features and related text material when the components were depicted mimetically (visually mimicking the real-world objects to which they refer) rather than through the use of labels.…”
Section: Maps and Diagrams As Symbol Systemsmentioning
confidence: 97%
See 2 more Smart Citations
“…Students tend to recall more factual information from a text or lecture when they are also able to study a related map (e.g., Abel & Kulhavy, 1986;Gilmartin. 1982: Kulhavy, Lee & Caterino, 1985.…”
mentioning
confidence: 99%